Influence of adult attachment insecurities on parenting self-esteem: the mediating role of dyadic adjustment - Calvo, Vincenzo; Bianco, Francesca (Frontiers in Psychology, 2015)
Background: Parenting self-esteem includes two global components, parents’ self-efficacy and satisfaction with their parental role, and has a crucial role in parent-child interactions. The purpose of this study was to develop an integrative model linking adult attachment insecurities, dyadic adjustment, and parenting self-esteem. Methods: The study involved 118 pairs (236 subjects) of heterosexual parents of a firstborn child aged 0 to 6 years. They were administered the Experiences in Close Relationships – Revised (ECR-R) questionnaire, the Dyadic Adjustment Scale (DAS), and the Parenting Sense of Competence Scale (PSOC). Results: Path analysis was used to design and test a theoretical integrative model, achieving a good fit with the data. Findings showed that dyadic adjustment mediates the negative influence on parenting self-efficacy of both attachment anxiety and attachment avoidance. Parenting satisfaction is positively influenced by parenting self-efficacy and negatively affected by child’s age. Attachment anxiety negatively influences parenting satisfaction. Conclusion: Our findings are in line with the theoretical expectations and have promising implications for future research and intervention programs designed to improve parenting self-esteem.